Implications of asymmetry risk for portfolio analysis and asset pricing - Fousseni Chabi-Yo; Dietmar Leisen; Eric Renault (Bank of Canada, 2007)
Asymmetric shocks are common in markets; securities'; payoffs are not normally distributed and exhibit skewness. This paper studies the portfolio holdings of heterogeneous agents with preferences over mean, variance and skewness, and derives equilibrium prices. A three funds separation theorem holds, adding a skewness portfolio to the market portfolio; the pricing kernel depends linearly only on the market return and its squared value. Our analysis extends Harvey and Siddique's (2000) conditional mean-variance-skewness asset pricing model to non-vanishing riskneutral market variance. The empirical relevance of this extension is documented in the context of the asymmetric GARCH-in-mean model of Bekaert and Liu (2004).
Keywords: C52; D58; G11; G12; 330; Financial markets; Market structure and pricing; Portfolio-Management; Kapitalanlage; Entscheidung bei Risiko; Asymmetrische Information; Marktstruktur; Theorie